Evaluation of potential antiviral properties of tualang honey against in vitro chikungunya virus infection in vero cells - Barkhadle, Najmo Ibrahim (2020)
Chikungunya is a mosquito-borne viral disease transmitted to human by CHIKV which has affected many countries around the world. CHIKV is transmitted mainly by two species of Aedes mosquitoes, Aedes albopictus and Aedes aegypti, and causes typically acute illness with incapacitating arthralgia, fever and rashes. Currently, there is no antiviral or licensed vaccine commercially available. In this study, we explored the in vitro antiviral activity of the Tualang honey against CHIKV in Vero cells. The potential anti-CHIKV property of Tualang honey was determined in different assays including virucidal, pre-treatment, post-treatment, anti- entry and anti-adsorption, using the non-toxic concentrations of Tualang honey at different incubation hours. The viral inhibitory effect was confirmed by plaque assay after morphological changes of Vero cells were observed. The results showed that Tualang honey was not toxic to Vero cells at concentration between 20 mg/mL to 5 mg/mL. This study demonstrated that Tualang honey exhibited significant antiviral activity against CHIKV. The virucidal activity of Tualang honey against different amounts of CHIKV was observed by the significant inhibition noticed in the viral titre. Remarkably, the pre-treatment of Tualang honey on Vero cells for 12 and 24 hours before infection gave the highest inhibitory effect on CHIKV especially at 48 hours post infection, with about 90% inhibition of viral titres was observed (P < 0.05). Surprisingly, during post-treatment assay, CHIKV replication was significantly inhibited in Vero cells following post-exposure to Tualang honey for 8 hours. The post-treatment of cells with Tualang honey displayed the biggest reduction of viral titre effect when compared with the other assays with percentage of inhibition 98% (P < 0.05). However, Tualang honey did not significantly inhibit infection of Vero cells by CHIKV during the anti-adsorption and anti-entry assay with percentage of inhibition surpassed 33 to 80%. Overall, the results from the current study suggest that Tualang honey can be explored as an alternative anti-CHIKV agent. Future study is warranted to elucidate Tualang honey mechanism of action and whether similar effects could be demonstrated in vivo.